Ending the Anomaly: Achieving Low Latency and Airtime Fairness in WiFi - Høiland-Jørgensen, Toke; Kazior, Michał; Täht, Dave; Hurtig, Per; Brunstrom, Anna (Karlstad University, 2018)
This is the dataset and companion website to the paper Ending the Anomaly: Achieving Low Latency and Airtime Fairness in WiFi which was published at USENIX ATC 17.

Also published at https://www.cs.kau.se/tohojo/airtime-fairness/
Keywords: Computer Sciences; Datavetenskap (datalogi)